Visual narrative of ethnic identity: preserving Chinese culture through traditional hand-drawn batik Lasem - Haryanti, Dwi Asih; Retno Ningsih, Tri Wahyu; Ayesa , Ayesa; Saptono , Debyo (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
Lasem, a coastal town in Central Java, Indonesia, is well known for its unique batik that blends cultural influences from both Chinese and Javanese. The study explores how traditional hand-drawn batik Lasem functions as a visual narrative representing Chinese ethnic identity and helps preserve culture in Indonesia’s diverse society. Through qualitative research, data were collected through purposive sampling of key informants, namely artisans and batik entrepreneurs at the ‘Kidang Mas’ batik center in Lasem. Data collection techniques include in-depth observation, semi-structured interviews, and visual documentation of the batik-making process. The researchers used thematic analysis to examine repeated patterns, cultural symbols, and meaning in the batik-making process. The findings exhibit cultural preservation in practices such as using canting tools, applying nature-based designs, and incorporating symbols from Chinese mythology. These motifs are decorative and tell stories regarding belief, values, and cultural identity. This study adds to discussions on intangible cultural heritage by showing that traditional batik is more than simply ‘an art’ but a living expression of Chinese-Indonesian identity. The combination of symbolic and local elements reflects cultural strength and adaptation, highlighting hand-drawn batik Lasem in keeping minority identities in Indonesia visible in Indonesia’s multicultural society.